Analisis Gharar Dalam Jual Beli Limbah Tambang Emas Di Kecamatan Muarasipongi Kabupaten Mandailing Natal - Fitri Nuri Aswari; Zul Anwar Ajim Harahap; Sawaluddin Siregar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study examines gharar in the sale and purchase of gold mine waste in Muarasipongi District, Mandailing Natal Regency in terms of Fiqh Muamalah. This research is a field research with a qualitative approach. The data obtained using primary data, namely data obtained from the village government, sellers (owners of galundung machines) and buyers. To complete this research, the author also uses secondary data, namely references such as books, journals, and related documents. Data collection is done by observation, interviews, and documentation. The data analysis technique is descriptive qualitative. The results of this study indicate that the sale and purchase of gold mining waste should be able to provide benefits to both buyers and sellers. However, when the buyer reprocesses the waste there is no gold content in it, because basically the seller does not know at all about the quality, quantity, or level of gold contained in the waste. So the buyer feels very disadvantaged due to the unclear object he bought. The sale and purchase of gold mining waste carried out by the people of Muarasipongi District, Mandailing Natal Regency is not valid because it contains gharar and does not meet the terms and conditions stipulated in the fiqh muamalah.